2008
DOI: 10.1038/ismej.2008.4
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary loss of the rdar morphotype in Salmonella as a result of high mutation rates during laboratory passage

Abstract: Rapid evolution of microbes under laboratory conditions can lead to domestication of environmental or clinical strains. In this work, we show that domestication due to laboratory passage in rich medium is extremely rapid. Passaging of wild-type Salmonella in rich medium led to diversification of genotypes contributing to the loss of a spatial phenotype, called the rdar morphotype, within days. Gene expression analysis of the rdar regulatory network demonstrated that mutations were primarily within rpoS, indica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
30
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 55 publications
2
30
0
Order By: Relevance
“…Next to the two clear sequence (cis) mutations, generating inactive csgB and csgD promoters, reflecting a different evolutionary lifestyle (no or minimal non-host environmental passage during lifecycle), six other isolates harboured upstream regulatory (trans) mutations, responsible for rdar phenotype loss, probably originating from domestication. In line with this, recent evidence indeed showed that rapid domestication due to laboratory passage in rich medium was responsible for the evolutionary loss of the rdar morphotype (Davidson, White, & Surette, 2008). This loss most of the times appeared to be related to mutations in rpoS, within the cellulose biosynthesis pathway or in unknown upstream rdar morphotype regulators.…”
Section: Csgdmentioning
confidence: 76%
“…Next to the two clear sequence (cis) mutations, generating inactive csgB and csgD promoters, reflecting a different evolutionary lifestyle (no or minimal non-host environmental passage during lifecycle), six other isolates harboured upstream regulatory (trans) mutations, responsible for rdar phenotype loss, probably originating from domestication. In line with this, recent evidence indeed showed that rapid domestication due to laboratory passage in rich medium was responsible for the evolutionary loss of the rdar morphotype (Davidson, White, & Surette, 2008). This loss most of the times appeared to be related to mutations in rpoS, within the cellulose biosynthesis pathway or in unknown upstream rdar morphotype regulators.…”
Section: Csgdmentioning
confidence: 76%
“…For pathogens like S. Typhimurium, the maintenance of a subset of cells primed for invasion but not ideally suited for environmental survival would impose a penalty unless a host is encountered. The energy commitment required to make SPI-1 T3SS organelles (82) or extracellular matrix polymers (83,84) in different subpopulations indicates that it might be a strategy for S. Typhimurium to prepare for unpredictability. A proportion of cells could survive exposure to either the host or nonhost environment, with the ultimate goal being preservation of the shared genome for the next generation (54,80).…”
Section: Discussionmentioning
confidence: 99%
“…3D and 4B). The energy theory arises from the observation that the capability to express multicellular behavior is easily lost under laboratory conditions (8,34). Although there is no doubt that production of extracellular matrix is energetically expensive, another reason for phenotypic heterogeneity can be to maintain the developmental potential of the population.…”
Section: Discussionmentioning
confidence: 99%